Deskripsi Logam Merkuri (HG) dalam Sampel Krim Pemutih Wajah dengan Metode ICP-OES - Grace Tandiseru; Wahidin Wahidin (An-Najat, 2024)
Chemical substances are used in whitening creams to brighten the skin and remove dark spots. Because mercury can prevent the skin from producing melanin, it is often used.The aim of this research is to determine the quantity and composition of mercury found in whitening creams sold at cosmetic outlets in the Sunter area. Using quantitative analysis through ICP-OES and organoleptic testing (texture, color, and odor), it was found that sample S5 contains 3460.14 mg/kg of mercury, while sample S7 contains 857.07 mg/kg. Both samples are considered hazardous for use because they do not meet the requirements set by the Head of the Food and Drug Supervisory Agency through Regulation No. 23 of 2019